A review on the application of nanofluids in vehicle engine cooling system - Che Sidik, Nor Azwadi (Elsevier Ltd, 2015)
This paper reviewed the application of nanofluids in vehicle engine cooling system. So far, nanoparticles have been used in engine oil, transmission oil, and radiator coolant to enhance heat transfer removal from vehicle engine. The heat transfer performance of nanofluids has been reported to perform better compared to pure fluid. This review focused on the experimental and numerical studies by previous researchers and their suggested amount of nanoparticles for optimum performance in vehicle engine cooling system. Finally, the conclusions and important summaries were presented according to the data collected.